Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/jbmr.4264
|View full text |Cite
|
Sign up to set email alerts
|

Tmem100- and Acta2-Lineage Cells Contribute to Implant Osseointegration in a Mouse Model

Abstract: Metal implants are commonly used in orthopedic surgery. The mechanical stability and longevity of implants depend on adequate bone deposition along the implant surface. The cellular and molecular mechanisms underlying peri‐implant bone formation (ie, osseointegration) are incompletely understood. Herein, our goal was to determine the specific bone marrow stromal cell populations that contribute to bone formation around metal implants. To do this, we utilized a mouse tibial implant model that is clinically repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Interestingly, Lrrc15 is also a marker for PPCs in our study. In addition, abundant αSMA+ stromal cells were recently reported to occur around the injury site after metal implant surgery in mouse tibiae ( Vesprey et al, 2021 ). In sum, acute injury resulting from bone fracture, metal implantation, or other insults appears to elicit a common and forceful repair response that is coupled to the emergence of progenitors with a myofibroblast-like phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Lrrc15 is also a marker for PPCs in our study. In addition, abundant αSMA+ stromal cells were recently reported to occur around the injury site after metal implant surgery in mouse tibiae ( Vesprey et al, 2021 ). In sum, acute injury resulting from bone fracture, metal implantation, or other insults appears to elicit a common and forceful repair response that is coupled to the emergence of progenitors with a myofibroblast-like phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies using immunostaining against TMEM100 in different human organs showed that TMEM100 is highly expressed in the human lung ECs but not in any other organ (heart, liver, kidney) ECs [ 14 ], suggesting that TMEM100 might play an important role in lung vasculature hemostasis. Moreover, several groups have generated Tmem100 reporter mouse lines [ 9 , 10 , 14 , 15 , 16 ] ( Table 1 ). Moon et al and Somekawa et al showed that Tmem100 reporter expression was detected in the major arteries in E10.5 and E11.5 embryos [ 9 , 10 ].…”
Section: Tmem100 and Its Expression Patternmentioning
confidence: 99%
“…Moon et al showed that Tmem100 expression was also found in the mammary glands, notochord, and ventral regions of the neural tube [ 9 ]. Vesprey et al employed a Tmem100-creERT2; Ai14 reporter mouse line and found that postnatal Tmem100-creERT2 expression marked endothelial cells, PaS cells, osteoblasts, and proliferating zone chondrocytes [ 16 ]. Through colocalization with a pan-neuronal marker, PGP9.5, Eisenman et al found the localization of TMEM100 immunoreactivity in the mice and human enteric nervous system and the mice’s central and peripheral nervous system in addition to arterial ECs [ 12 ].…”
Section: Tmem100 and Its Expression Patternmentioning
confidence: 99%